PENGARUH VARIASI BARREL TEMPERATURE, INJECTION PRESSURE DAN COOLING TIME TERHADAP CACAT WARPAGE PADA PROSES INJECTION MOLDING (AL-PP) - Saputra, Dheo Ardi Nugraha; Sutjahjono, Hary; Yudistiro, Danang; Rozy H, M Fahrur; Noor HS, Skriptyan (STATOR: Jurnal Ilmiah Teknik Mesin, 2024)
Plastic is a polymer that has unique and extraordinary characteristic properties. With a binder (plastic) can be combined with metal elements, namely aluminum. Aluminum is chosen as an alloy material because it has good strength and tenacity. Metal alloy plastic can be processed by a method called injection molding. Injection molding is a process used in making plastic products. This research was conducted with barrel temperature, injection pressure and cooling time process variables. While the response variable is warpage defects. This study aims to determine the effect of variations in process parameters is barrel temperature, injection pressure, cooling time on warpage defects in injection molding products with Al-PP alloy material, and find out the optimum variation of parameters in the injection molding process. The results showed that barrel temperature had an effect of 91.62% on the value of warpage defect response, this condition can be observed as the level barrel temperature increases, the value of warpage defects also increases. The effect of 6.43% injection pressure on the value of warpage defects due to an increase in each injection pressure level will reduce the chance of warpage defects. The effect of cooling time parameters is 1.78% on the value of warpage defects, which means that the longer the cooling time, the greater the response or warpage produced. The optimum variation of parameters in the injection molding process in the ASTM A370 test specimen in barrel temperature parameters at level 1 is 150 oC, the injection pressure parameter at level 3 is 11 bar and the cooling time parameter at level 1 is 15 seconds.